Self-Compassion sebagai Faktor Penentu Kepuasan Hidup Driver Ojek Online di Kota Palembang pada Masa New Normal - Ully Astri; Indra Prapto Nugroho (Psychology Journal of Mental Health, 2025)
Abstract. This study aims to determine whether there is a role of self-compassion on life satisfaction of online motorcycle taxi drivers during the new normal period in Palembang. The hypothesis of this research is that there is a role of self-compassion on life satisfaction of online motorcycle taxi drivers during the new normal period in Palembang. Respondents in this study amounted to 150 online motorcycle taxi drivers in the city of Palembang. The sampling technique used was purposive sampling. This study uses two main scales as a measuring tool, namely the Life Satisfaction scale which refers to the aspects of Neugarten, Havighurst, & Tobin (1982) and the self-compassion scale which refers to the components of Neff (2003). The results of the regression analysis showed that the value of R square = 0.179 and p = 0.000 (p <0.05). The results of the analysis indicate that self-compassion has a significant role on life satisfaction. Thus, the hypothesis proposed in this study can be accepted.